2015
DOI: 10.1115/1.4030693
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Characterization of a Photovoltaic Array Based on Actual Performance Using Cascade-Forward Back Propagation Artificial Neural Network

Abstract: This paper proposes a novel prediction model for photovoltaic (PV) system output current. The proposed model is based on cascade-forward back propagation artificial neural network (CFNN) with two inputs and one output. The inputs are solar radiation and ambient temperature, while the output is output current. Two years of experimental data for a 1.4 kWp PV system are utilized in this research. The monitored performance is recorded every 2 s in order to consider the uncertainty of the system's output current. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…To validate the effectiveness of the proposed model, its performance in terms of MAPE compared with some of the research works in the same area. Here, the proposed model compared with perturb and observe (P&O) method with incremental conductance method (ICM) [38], random forests (RFs) model [4], generalized regression artificial neural network (GRNN) [30] and CFNN [30] as listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the effectiveness of the proposed model, its performance in terms of MAPE compared with some of the research works in the same area. Here, the proposed model compared with perturb and observe (P&O) method with incremental conductance method (ICM) [38], random forests (RFs) model [4], generalized regression artificial neural network (GRNN) [30] and CFNN [30] as listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The number of hidden neurons is considered one of the essential hyper-parameters in the ANN, which significantly affects the ANN models' accuracy. According to the literature, no mathematical formula can be used to find the optimal number of hidden neurons directly [30]. The number of hidden neurons is dependent on the data characterization and the number of inputs, outputs, and hidden layers.…”
Section: Cascade-forward Neural Network (Cfnn)mentioning
confidence: 99%
“…The modelling for operating temperature has attracted more and more attention [10][11][12], and many researchers have explored the operating temperature calculation methods of silicon-based PV modules. Reference [13] used the theoretical model of silicon-based PV modules to calculate the operating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Their experiments and proposed model results are close to the actual results with small percentage error. Several researchers are implementing supervised feed forward ANN techniques to forecast solar energy production [11][12][13]. Artificial neural networks (ANN) have become increasingly useful for system modelling and the optimization of results.…”
Section: Related Artificial Neural Network-based Workmentioning
confidence: 99%
“…The results of the experiments and numerical models showed that the percentage of energy saving is about 15% in North European weather conditions. Khatib et al [12] proposed a solar irradiation, system-based ANN, which uses data from 28 cities in Malaysia. The proposed neural network model is used to forecast the clearness index, which is used to establish a predictive global solar irradiation system for Malaysia.…”
Section: Related Artificial Neural Network-based Workmentioning
confidence: 99%